Perkembangan Teknologi Penangkapan Ikan dan Dampaknya terhadap Kehidupan Sosial Ekonomi Masyarakat Nelayan Muara Kandis Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan Tahun 2011-2018 - Widya Fitri; Najmi Najmi (PAMA Aksara, 2021)
This research examines the development of fishing technology in Muara Kandis from 2011-2018 and its impact on the socio-economic life of fishermen. This research is important to do to find out the activities of fishermen, the emergence of modernization and development of fishing gear and how it impacts the lives of fishing communities in the social, economic and educational fields in Muara Kandis. The method used in this research is the historical method. First, Heuristics is the stage of collecting data in the form of primary data and secondary data. Second, source criticism is the stage of processing data or information through internal and external criticism. Third, interpretation or data analysis. Fourth, historiography or historical writing is the stage of writing research reports into scientific writing in the form of a thesis. The results showed that the people in Nagari Muara Kandis depend a lot on their lives as fishermen because the area is located on the coast. The development of fishing technology began to be felt by the fishing community in early 2011 with the entry of motorized boats known as outboard engines. These developments certainly cannot be separated from the role of the government where counseling is held by the Ministry of Marine Affairs and Fisheries in collaboration with the local government on the use of modern technology. With the development of this technology, of course, it has an impact on the socio-economic life of fishermen, such as increased economic income, well-established social relations between fellow fishermen and with the surrounding community as well as impacts in the field of education.